2019
DOI: 10.9734/ajraf/2019/v4i130053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Moisture Harvesting Techniques on Seedling Survivals and Growth of Trees in Degraded Lands of Southern Tigray

Abstract: Tree planting on degraded lands play a key role in forest rehabilitation processes through afforestation and/or reforestation. Moisture harvesting structures (MHSs) has significant impact on seedling survivals at degraded lands. The objectives of this study were to investigate the impact of water harvesting techniques on seedling survival and growth performance of trees. Field experiments were conducted for two rainy seasons in southern Tigray, Atsela watershed. The experimental design followed was the split p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although many rainwater harvesting structures are used to conserve soil and water in degraded lands, research findings have shown variability in their effectiveness for plant growth, biomass production, restoration of degraded lands, etc. [14,21,24,27]. This result shows that the extent to which different soil and water conservation structures influence plant growth and rehabilitation on severely degraded lands needs to be further investigated, as their effect could vary depending on the severity of the degraded land, precipitation pattern, and the type of planted species used for restoration.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although many rainwater harvesting structures are used to conserve soil and water in degraded lands, research findings have shown variability in their effectiveness for plant growth, biomass production, restoration of degraded lands, etc. [14,21,24,27]. This result shows that the extent to which different soil and water conservation structures influence plant growth and rehabilitation on severely degraded lands needs to be further investigated, as their effect could vary depending on the severity of the degraded land, precipitation pattern, and the type of planted species used for restoration.…”
Section: Introductionmentioning
confidence: 93%
“…Problems related to land degradation can be prevented by using various mechanisms and activities [13], such as maximizing vegetation cover in degraded lands which should be given a priority since this action can prevent erosion and replace soil nutrients removed by erosion [4,14,15]. However, to maximize vegetation cover through natural regeneration and artificial plantations, factors such as shortages in soil nutrients and limited available water during the dry season in degraded lands affect the restoration process [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result contrasts with the study in dry areas of East Shoa zone where the survival percentages of four types of promising multipurpose trees that is, Azadirachta indica, Schinus molle, Acacia saligna and Parkinsonia aculeata were highest in semicircular bund and contour-bench and, least performed in infiltration pits (Abera and Fitih, 2015). In-situ rainwater harvesting devices are important in facilitating favorable conditions for plant growth as well as tree seedling survival in moisture-stress areas (Demisachew et al, 2018).…”
Section: Effects Of Soil and Moisture Conservation Structures On The Survival Rate Of Planted Speciesmentioning
confidence: 99%
“…Successful tree seedling survival and growth depend on the soil condition and stored soil moisture available to ensure tree seedling survival dry season (Warren et al, 2005). In the degraded lands of Borana rangeland, pastoralists have been planting many tree seedlings species year after year (Demisachew et al, 2018). However, the survival of those seedlings is poor and variable as the area is mainly affected by moisture stress problems.…”
Section: Introductionmentioning
confidence: 99%